Philanthropy and Sustainable Compassion: An Evidence of Charity Activism in Alumni Association of Islamic Boarding School - Eja Armaz Hardi; Masnidar Masnidar; Efni Anita (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
Charity activism has been growing significantly since the pandemic covid-19 outbreak in the early 2020s among Indonesian Muslims. Not only state and non-state actors have taken a role to lessen covid-19-victims’ drawbacks through Islamic social finance, but also private organization and association have done the same. The purpose of this paper is to examine the sustainable charity of Azzavirtium Endowment Fund (Dana Abadi Azzavirtium/DAZZ), which has initiated by the 2004 alumni association of Darussalam Gontor Boarding School (Pondok Modern Darussalam Gontor/PMDG). Employing the model of Participation Action Research (PAR), this paper argues that the DAZZ's endowment fund management has given the pattern of sustainable Islamic social finance. Furthermore, this paper argues that the endowment fund has impacted on raising of sustainable compassion activism among alumni members, families, and even for the second generation. It further found that the orphans sponsoring has done with a textual understanding of religious orders without adding another material consideration.